Fifty Years of Climate Change Studies: A Scientometric Assessment - Sulaimon Oyeniyi Adebayo; Hardeep Singh; Supreet Kaur; Himanshi Sharma; Jai Sharma; Karman Singh Sethi (IEEE Access)
Over the years, climate change has emerged as a critical area of research, marked by rapid growth in both interest and scholarly output. This surge has resulted in an extensive body of scientific literature addressing diverse aspects of the field. To better understand the evolution, development, and current landscape of climate change studies, it is essential to examine the structure and trends within this expanding corpus. Despite the increasing volume of publications, comprehensive scientometric assessments in this domain remain limited. Addressing this gap, the present study conducts a scientometric analysis of 437,035 climate change-related research documents indexed in Scopus, covering a 50-year period (1972-2021). The study analyzes annual publication trends, subject classifications, geographical and linguistic distributions, and various bibliometric attributes. In addition, advanced analyses using the VOSviewer tool investigate citation patterns, authorship trends, keyword co-occurrences, research contributions, and collaborative networks. The results highlight an average annual growth rate of 14.3%, with over 69% of the total publications produced in the last decade (2012-2021). English accounts for 95.2% of all publications, followed by Chinese (1.8%) and German (0.6%). The United States leads in research output, contributing 19.18% of total publications, followed by China (8.18%) and the United Kingdom (8.00%). Citation and collaboration analyses further examine institutional output and international research networks. Nature, Science, and Journal of Climate emerged as the most influential journals, while leading institutions include the National Center for Atmospheric Research (USA), the University of East Anglia (UK), and the Chinese Academy of Sciences. Prominent authors such as Philippe Ciais, Josep Peñuelas, and Pete Smith are also recognized for their significant contributions. By providing a comprehensive overview, this study reveals key trends and collaborative patterns that have shaped climate change research over the last five decades, offering valuable insights to academics, research institutions, and policymakers for advancing future research and global cooperation in this vital field.